Theoretical basis for using information and communication technologies in the process of teaching chemistry - Sadokat, Faizulloeva (Goodwood Publishing, 2025)
Purpose: This study aims to establish a theoretical foundation for integrating ICT in chemistry education by examining its pedagogical value, identifying best practices, and presenting strategies for effective implementation. Research methodology: A mixed-methods design was applied using purposive sampling of secondary school chemistry teachers and students in Ghana. Quantitative data were collected through questionnaires and pre-post tests, and qualitative data were collected through interviews and classroom observations. ICT tools such as virtual labs, simulations, and digital platforms were explored and applied through blended and inquiry-based learning strategies. Data were analyzed using SPSS for quantitative evaluation and thematic analysis for instructional practices and teacher’s readiness. Results: The findings indicate that ICT integration, including virtual laboratories and simulations, significantly improves student engagement and conceptual understanding. It supports constructivist and inquiry-based approaches, fostering critical thinking and collaboration among students. Challenges remain in terms of technology accessibility and the ongoing need for teacher training. Conclusions: This study establishes a theoretical framework for ICT in chemistry education, linking it to pedagogical models. The best practices identified enhance engagement, conceptual learning, and critical thinking. Proper ICT implementation can improve teaching effectiveness and learning outcomes. Limitations: This study relies on existing literature and secondary data without direct classroom interventions and faces constraints in low-resource contexts with limited ICT access. Contribution: This study advances theoretical and practical insights into ICT’s role of ICT in enhancing chemistry education through engagement, deeper learning, and modern pedagogical alignment.